The Economics of the Manuscript and Rare Book Trade, ca. 1890-1939 - Botana, Federico; Cleaver, Laura (Collection Development, Cultural Heritage, and Digital Humanities, 2024)
The market for rare books has been characterized as unpredictable, and driven by the whims of a small number of rich individuals. Yet behind the headlines announcing new auction records, a range of sources make it possible to analyze the market as a whole. This book introduces the economics of the trade in manuscripts and rare books during the turbulent period ca. 1890-1939. It demonstrates how surviving sources, even when incomplete and inconsistent, can be used to tackle questions about the operation of the rare book trade, including how books were priced, profit margins, accounting practices, and books as investments, from the perspectives of both dealers and collectors.